1999
DOI: 10.1038/sj.bjc.6690687
|View full text |Cite
|
Sign up to set email alerts
|

Potent interaction of flavopiridol with MRP1

Abstract: The multidrug resistance protein 1 (MRP1) is an ATP-dependent transport protein for organic anions, as well as neutral or positively charged anticancer agents. In this study we show that flavopiridol, a synthetic flavonoid currently studied in phase 1 trials for its anti-proliferative characteristics, interacts with MRP1 in a potent way. Flavopiridol, as well as other (iso)flavonoids stimulate the ATPase activity of MRP1 in a dose-dependent way at low micromolar concentrations. A new specific monoclonal antibo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
2
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 42 publications
2
58
2
1
Order By: Relevance
“…51 and 52) of flavopiridol may be due to inhibition of intracellular mechanisms other than CDK activity. These include inhibition of glycogen phosphorylase (26,27), GSK-3␣/␤ (10), and cytosolic aldehyde dehydrogenase (25) as well as interaction with multidrug resistance protein 1 (53,54). Similarly, an affinity chromatography approach recently allowed us to identify Erk2 as a major intracellular target of the CDK inhibitor purvalanol (24).…”
Section: Fig 9 Gwennpaullone-binding Proteins In L Mexicana (A) Anmentioning
confidence: 99%
“…51 and 52) of flavopiridol may be due to inhibition of intracellular mechanisms other than CDK activity. These include inhibition of glycogen phosphorylase (26,27), GSK-3␣/␤ (10), and cytosolic aldehyde dehydrogenase (25) as well as interaction with multidrug resistance protein 1 (53,54). Similarly, an affinity chromatography approach recently allowed us to identify Erk2 as a major intracellular target of the CDK inhibitor purvalanol (24).…”
Section: Fig 9 Gwennpaullone-binding Proteins In L Mexicana (A) Anmentioning
confidence: 99%
“…We and others have previously reported that a wide range of flavonoids can inhibit the conjugated organic anion transport properties and modulate the ATPase activity of MRP1 (Hooijberg et al, 1997(Hooijberg et al, , 1999(Hooijberg et al, , 2000Leslie et al, 2001a). Thus a number of bioflavonoids were found to be potent inhibitors of LTC 4 and 17␤-estradiol 17-(␤-D-glucuronide) transport by MRP1-enriched membrane vesicles (Leslie et al, 2001a).…”
mentioning
confidence: 99%
“…Such apparently contradictory effects were previously also observed for other flavonoids, e.g. kaempferol, apigenin and flavopiridol [9,59]. At present, there is no satisfactory explanation of such observations (see Leslie et al [9] and discussion within).…”
Section: Discussionmentioning
confidence: 56%